Multisectoral action for health in low-income and middle-income settings: how can insights from social science theories inform intragovernmental coordination efforts? - Ssennyonjo, Aloysius; Van Belle, Sara; Titeca, Kristof; Criel, Bart; Ssengooba, Freddie (BMJ Global Health, 2021)
There is consensus in global health on the need for multisectoral action (MSA) to address many contemporary development challenges, but there is limited action. Examples of issues that require coordinated MSA include the determinants of health conditions such as nutrition (malnutrition and obesity) and chronic non-communicable diseases. Nutrition, tobacco control and such public health issues are regulated separately by health, trade and treasury ministries. Those issues need to be coordinated around the same ends to avoid conflicting policies. Despite the need for MSA, why do we see little progress? We investigate the obstacles to and opportunities for MSA by providing a government perspective. This paper draws on four theoretical perspectives, namely (1) the political economy perspective, (2) principal–agent theory, (3) resource dependence theory and (4) transaction cost economics theory. The theoretical framework provides complementary propositions to understand, anticipate and prepare for the emergence and structuring of coordination arrangements between government organisations at the same or different hierarchical levels. The research on MSA for health in low/middle-income countries needs to be interested in a multitheory approach that considers several theoretical perspectives and the contextual factors underlying coordination practices.
Keywords: Multisectoral action; Nutrition; middle-income settings; intragovernmental